Decoupled elastic prestack depth migration - Druzhinin, Alexander (Journal of applied geophysics, 2003)
This paper presents a new decoupled form of the formula for common-shot or common-receiver amplitude-preserving elastic prestack depth migration (PreSDM), which can be used for estimating angle-dependent elastic reflection coefficients in laterally inhomogeneous anisotropic media. The multi-shot or multi-receiver extension of this formula is suitable for automated prestack amplitude-versus-angle (AVA) elastic inversion of ocean-bottom cable (OBC), walkaway VSP (WVSP) or standard towed-cable data at any subsurface location. The essence of the theory is a systematic application of the stationary-phase principle and high-frequency approximations to the basic elastic Green's theorem. This leads to nonheuristic explicit wave mode decoupling and scalarization of vector PreSDM. Used in combination, ray-trace and finite-difference (FD) eikonal solvers create a useful tool to calculate accurate Green's function travel time and amplitude maps. Examples of synthetic OBC data and applications to field WVSP data show that the new imaging technique can produce a clear multi-mode elastic image.